The Therapy and Management of Heart Failure with Preserved Ejection Fraction: New Insights on Treatment - Giulio Balestrieri; Raul Limonta; Enrico Ponti; Anna Merlo; Edoardo Sciatti; Salvatore D’Isa; Mauro Gori; Gavino Casu; Cristina Giannattasio; Michele Senni; Emilia D’Elia (Cardiac Failure Review)
Heart failure with preserved ejection fraction (HFpEF) is a clinical syndrome characterised by the presence of diastolic dysfunction and elevated left ventricular filling pressure, in the setting of a left ventricular ejection fraction of at least 50%. Despite the epidemiological prevalence of HFpEF, a prompt diagnosis is challenging and many uncertainties exist. HFpEF is characterised by different phenotypes driven by various cardiac and non-cardiac comorbidities. This is probably the reason why several HFpEF clinical trials in the past did not reach strong outcomes to recommend a single therapy for this syndrome; however, this paradigm has recently changed, and the unmet clinical need for HFpEF treatment found a proper response as a result of a new class of drug, the sodium–glucose cotransporter 2 inhibitors, which beneficially act through the whole spectrum of left ventricular ejection fraction. The aim of this review was to focus on the therapeutic target of HFpEF, the role of new drugs and the potential role of new devices to manage the syndrome.